Guidelines for writing effective operating and maintenance procedures. (Center for Chemical Process Safety, American Institute of Chemical Engineers, 1996)
The EPA investigation of a 1994 chemical plant tragedy concluded that ""the explosion resulted from a lack of written safe operating procedures ... "" While good written procedures can't guarantee zero accidents, they can reduce the number of accidents caused by human error. This new book shows how to remedy this problem through selecting and implementing actions that promote safe, efficient operations and maintenance, improve quality, continuity, profitability and cost control, build upon and record process experience, and promote the concept that operating and maintenance procedures are vital pl.
Keywords: Chemical engineering -- Safety measures -- Handbooks, manuals, etc.; Technical writing -- Handbooks, manuals, etc.; elektronické knihy; electronic books